International journal of virtual communities and social networking - IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2009)
Virtual communities and social networking are changing our social and work environments. The International Journal of Virtual Communities and Social Networking (IJVCSN) provides a forum for researchers, practitioners, and users to study and discuss technical, social and legal issues in this fast changing environment. IJVCSN strives to be an inter-disciplinary journal that draws upon research from different fields such as information systems, computer science, sociology, and psychology.
Also available in print.
Mode of access: World Wide Web.
Description based on: Vol. 1, no. 1 (Jan./Mar. 2009); title from title screen (IGI Global, viewed Oct. 1, 2010).
Latest issue consulted: Vol. 2, no. 2 (Apr./June 2010).
Keywords: Online social networks -- Periodicals; Internet -- Social aspects -- Periodicals; Cross-cultural studies; Design issues; Design of peer-to-peer networks; Design of virtual communities; Mobile technologies and HCI; User friendly interfaces; Business models; E-learning models; Knowledge management models; Technology-based models; Copyright issues; Privacy issues; Trust issues; Economic impact of virtual communities; Individual behavior and group dynamics in virtual communities; Political impact of virtual communities; Social impact of virtual communities; Social network analysis; Social structures; Game design; Computer-based simulated environments; Social and cultural issues; Electronic books